1,2-Bis[(3,5-diphenyl-1H-pyrazol-1-yl)methyl]benzene - Lara C. Spencer (Acta Crystallographica Section E, 2012)
The title compound, C38H30N4, a potentially mono- and bidentate ligand, does not seem to form palladium complexes similar to other poly(pyrazol-1-ylmethyl)benzenes due to the large steric size of the phenyl substituents on the pyrazole rings. The pyrazole rings have a 21.09 (5)° angle between their mean planes and exhibit a trans-like geometry in which the in-plane lone pairs of electrons on the 2-N nitrogen atoms point in opposite directions.